Ameliorative effect of statin therapy on oxidative damage in heart tissue of hypercholesterolemic rabbits - Sozer, Volkan (WILEY-BLACKWELL, 2015)
The aim of this study was to investigate the effects of a high-cholesterol diet in the presence and absence of statin on Cu-Zn-superoxide dismutase (Cu, Zn-SOD), malondialdehyde (MDA), protein carbonyl (PCO), and nitric oxide (NO) of blood and heart tissue, the antioxidant activity of serum paraoxonase-1 (PON-1), and on the blood lipid profile of rabbits. The animals were divided into four groups each of which included 10 rabbits. Rabbits in group 1 received a regular rabbit chow diet (normal diet) for 8 weeks; those in group 2 received atorvastatin (0.3 mg atorvastatin per day/kg body weight) for 8 weeks; those in group 3 received high-cholesterol diet for 8 weeks; and those in group 4 received high-cholesterol diet for 4 weeks, a high-cholesterol diet + atorvastatin (0.3 mg atorvastatin per day/kg body weight) for 8 weeks. The parameters were measured by spectrophotometric methods. As expected, the atherogenic diet caused a pronounced increase in lipid profile (not HDL) parameters. Rabbits in group 3 showed higher PCO, MDA, and NO levels in circulating and heart tissue compared to the rabbits in group 1. Atorvastatin has prevented or limited LDL oxidation and has showed constitutively beneficial effects in group 4. Increased LDL-C, PCO, MDA, and NO levels leading to decreasing PON-1 activity thus create a predisposition to atherogenesis in this model. But atorvastatin administration partly ameliorated oxidative damage in heart injury of hypercholesterolemic rabbits. Atorvastatin which functions as a potent antioxidant agent may inhibit this LDL-C oxidation by increasing PON-1 activity in atherogenesis.
Keywords: atorvastatin; hypercholesterolemia; malondialdehyde; paraoxonase-1; protein carbonyl; CHOLESTEROL-FED RABBITS; NITRIC-OXIDE CONCENTRATION; SHORT-TERM TREATMENT; C-REACTIVE PROTEIN; SUPEROXIDE-DISMUTASE; PARAOXONASE ACTIVITY; ATORVASTATIN THERAPY; DENSITY-LIPOPROTEIN; DNA-DAMAGE; HYPERLIPIDEMIC RABBITS; Pharmacology & Pharmacy